Cutting edge: TLR13 is a receptor for bacterial RNA - Hidmark, Asa S.; Saint Paul, Antonia von; Dalpke, Alexander (The journal of immunology, 2012)
Bacterial RNA (bRNA) can induce cytokine production in macrophages and dendritic cells (DCs) through a previously unidentified receptor. Gene expression analysis of murine DCs showed that bRNA induced gene regulation similar to that induced by stimulation of TLR7 with R848. Although TLR7 was dispensable for cytokine induction by bRNA, TLR-associated proteins MyD88 and UNC93B were required. TLR13 is an endosomal murine TLR that has been described to interact with UNC93B with, so far, no characterized ligand. Small interfering RNA against TLR13 reduced cytokine induction by bRNA in DCs. Moreover, Chinese hamster ovary cells transfected with TLR13, but not with TLR7 or 8, could activate NF-κB in response to bRNA or Streptococcus pyogenes in an RNA-specific manner. TLR7 antagonist IRS661 could, in addition, inhibit TLR13 signaling and reduced recognition of whole Gram-positive bacteria by DCs, also in the absence of TLR7. The results identify TLR13 as a receptor for bRNA.
Gesehen am 19.06.2018